Comparison of two-dimenzional and three-dimensional echocardiography in determination od left ventricle volumes and ejection fraction in adult population. - Bushljetikj O; Georgievska-Ismail, Lj (Macedonian Academy of Sciences and Arts, 2017)
Introduction: Left ventricle (LV) volumes and ejection fraction (EF) determined with two-dimensional echocardiography (2DE) and three-dimensional echocardiography (3DE) show significant differences.The aim of this study is to determine the agreement of the measurements of LV volumes and EF with 2DE and 3DE in the general adult population, with preserved LV systolic function. Material and methods: In 52 subjects, older than 65 years, LV end-diastolic volume index (EDVi), end-systolic volume index (ESVi) and EF were measured with 2DE and 3DE according to the official recommendations, and reproducibility of both methods and their agreement were determined. Results: Intraclass correlation coefficient for intra-observer reproducibility in the measurement of EDVi, ESVi and EF with 2DE was 0.861, 0.891 and 0.917 respectively, whereas with 3DE 0.854, 0.893 and 0.913, respectively. The difference in the measurement of EDVi and ESVi was significant (p<0.001) whereas the measurement of EF was insignificant (p=0.153). The mean difference value EDVi and ESVi determined with 2DE and 3DE was 5.6+/-5.21 and 3.01+/-2.69 ml/m2 (p<0.001), and of EF 0.306+/-1.475%. Spear- man’s correlation coefficient for EDV was 0.693, for ESV 0.763 and for EF 0.97. Conclusion: Larger LV volumes were measured in the adult population using 3DE compared to 2DE, but identical values for EF were obtained. This difference in the measured values could not be attributed to the largeness of the LV volume and EF itself.. 3DE demonstrated better intra-observer reproducibility for LV volumes and EF as a major parameter in many clinical decisions.
Keywords: Three-dimensional echocardiography; Left ventricle volume